Major and trace (including arsenic) groundwater chemistry in central and southern Myanmar. (April 2020) - Pincetti-Zúniga, Gianfranco P.; Richards, Laura A.; Tun, Yin Min; Aung, Hla Phone; Swar, Aung Kyaw; Reh, U. Phyar; Khaing, Thet; Hlaing, Moe Moe; Myint, Tin Aung; Nwe, Myat Lay; Polya, David A.
Abstract: Myanmar, in Southeast Asia, is categorized as a Least Developed Country, facing substantial challenges towards meeting 2030 Sustainable Development Goal targets, including ensuring access to safe water and sanitation. The occurrence of geogenic contaminants, notably arsenic, in Myanmar groundwaters is relatively poorly understood, particularly as compared to other countries in South/Southeast Asia. Improving the understanding of groundwater quality in Myanmar is hence a major concern and relevant to the health of millions of local inhabitants who extensively use groundwater. A groundwater survey was undertaken at 85 sites across five distinctly contrasting zones within three of Myanmar's main river basins (Chindwin-Ayeyarwady, Sittaung, and Salween) to assess the occurrence of arsenic and other potentially harmful elements, and to study the dominant geochemical controls in each zone/basin. A significant number of samples were affected by water quality issues, based on World Health Organization (WHO) guidelines, including elevated arsenic (>10 μg.L −1 ) in 14% of all samples within the basins studied. Fluoride, nitrate, salinity, iron, manganese, and aluminum also exceeded WHO drinking water guidelines in some locations. Arsenic typically occurred as inorganic As III and largely arose from the reductive dissolution of Fe(Mn)-(hydro)xides and was broadly associated with relatively high HCO3 and NH4 . Variable dominant geochemical controls on groundwater composition were identified, notably (i) calcite and dolomite dissolution in the Salween basin; (ii) cation exchange, carbonate dissolution and saline intrusion in the Ayeyarwady delta; and (iii) gypsum dissolution, silicate weathering, and cation exchange in Chindwin-Middle Ayeyarwady. This reconnaissance study provides new information on groundwater composition and corresponding geochemical controls across contrasting, and previously underrepresented, areas of Myanmar and may help to inform further hazard assessment, monitoring and/or mitigation strategies. Graphical abstract: Image 1 Highlights: Study of groundwater inorganic quality in 5 contrasting zones in Myanmar. Arsenic >10 μg.L −1 mostly in Ayeyarwady delta and confirmed in other localized areas. High arsenic broadly consistent with reductive dissolution of iron-(hydro)xides. Other groundwater quality concerns include fluoride, manganese, and iron.